Unrealistic self-overconfidence in schizophrenia is associated with left presubiculum atrophy and impaired episodic memory. (January 2017) - Orfei, Maria Donata; Piras, Fabrizio; Banaj, Nerisa; Di Lorenzo, Giorgio; Siracusano, Alberto; Caltagirone, Carlo; Bandinelli, Pier Luca; Ducci, Giuseppe; Spalletta, Gianfranco
Abstract: The study aimed at investigating the role of the hippocampal subfields in cognitive insight and the clinical and neuropsychological underpinnings of the related two sub-dimensions, Self-Reflectiveness (SR), i.e., openness to external feedback, and Self-Certainty (SC), i.e., unrealistic overconfidence in one's opinions. In order to do this, 45 patients with a diagnosis of schizophrenia and 45 age- and gender-matched healthy control subjects (HC) were administered the Beck Cognitive Insight Scale (BCIS), along with neuropsychological, clinical and psychopathological assessment, and underwent an MRI investigation. Hippocampal segmentation was carried out. Regression analyses were performed for BCIS indexes, volumetric parameters of hippocampal subfields and clinical and neuropsychological variables. Results highlighted that in the schizophrenia group, higher levels of SC were related to reduced volume of the left presubiculum, and worse episodic memory. No significant relationship emerged for the SR index. There was no significant relationship between any of the BCIS indexes and volumetric data of the hippocampal subfields in the HC group. Our data support the hypothesis that unrealistic self-overconfidence in schizophrenia is related to the hippocampal presubiculum atrophy, which is involved in episodic memory and cognitive control and is supposed to be underpinned by difficulty in integrating new memories and thus in generating new hypotheses about the self.